2022
DOI: 10.1093/scipol/scac045
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating space for knowledge co-production

Abstract: Despite increased popularity of knowledge co-production as a research approach to address contemporary environmental issues, its implementation in science–policy contexts is not self-evident. In this paper, we illustrate how researchers at the PBL Netherlands Environmental Assessment Agency (in Dutch: Planbureau voor de Leefomgeving (PBL)) ensured a fit between key features of knowledge co-production and conventional norms and customs for knowledge production processes at the science–policy interface while sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Being able to build this hub on previous programs through an evolution from those past experiences (see Campbell et al, 2015) is an enabler of success through improved relationships, processes, and governance structures. It shows that not only a KE‐oriented funding program but also co‐production capacity develops over time with observation, reflection, and improvement (Verwoerd et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Being able to build this hub on previous programs through an evolution from those past experiences (see Campbell et al, 2015) is an enabler of success through improved relationships, processes, and governance structures. It shows that not only a KE‐oriented funding program but also co‐production capacity develops over time with observation, reflection, and improvement (Verwoerd et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Disciplinary silos further perpetuate tensions between transdisciplinary theory and practice. There are entrenched ways of knowing and doing within all (unitary) disciplines, which make using transdisciplinary approaches challenging for many scholars (Verwoerd et al, 2023). For example, Haeffner and colleagues (2022) documented the challenges quantitative, positivist-oriented scientists faced when asked to engage with qualitative autoethnography.…”
Section: Figure 1 the Requisite Qualities Of Transdisciplinary Researchmentioning
confidence: 99%
“…Transdisciplinary research has also been successful within policy settings, as demonstrated by Verwoerd and colleagues' study with a Dutch environment agency (2023). They demonstrated how scientists and policy administrators could collaborate to create effective policies supporting scientific rigour through planning, acting, observing, and reflecting (Verwoerd et al, 2023).…”
Section: Leadershipmentioning
confidence: 99%
“…Indeed, how irresistible is it to be able to present an improvement of sciencepolicy arrangements in a way that transforms them into an ostensible objective account, to 'fit and conform' improvements by aligning them with dominant modernist norms (cf. Smith and Raven, 2012;Kunseler, 2017;Verwoerd et al, 2022). But by depoliticizing the role of science-policy arrangements, we also lose the ability to ask what role we want science-policy arrangements to play.…”
Section: (Re)thinking and (Re)making Science-policy Arrangementsmentioning
confidence: 99%
“…The risk that transformative initiatives become partly co-opted into dominant modes of working, and thus, get partly stripped of their transformative potential is illustrated in Verwoerd's (2022) in-depth study of the normalization of 'reflexive evaluation' at PBL. 17 Verwoerd's work not only shows how reflexive evaluation has become an acceptable policy evaluation repertoire within the institute, but also points out how this repertoire has been adjusted throughout in order to align it more neatly with dominant norms (see also Verwoerd et al, 2022), i.e. the aforementioned problematic modernist assumptions.…”
Section: How To Create and Seize Opportunities For Transformative Cha...mentioning
confidence: 99%